Art cinema and India's forgotten futures : film and history in the postcolony - Majumdar, Rochona (Columbia University Press, 2021)
"In the years following Indian independence in 1947, art cinema was seen as central to the development and future of the new nation. Filmmakers like Satyajit Ray came to the fore as did a host of film societies and publications aimed at promoting a new kind of film culture that would offer a distinct alternative to the popular movies coming out of Bombay. Indian art film would not only bring the new nation international prestige but would create responsible and discerning individuals capable of exercising and combining aesthetic and political judgments. Good films, it was believed, could produce good citizens. However, as Rochona Majumdar argues, the liberal faith of progress championed by Indian elites in the 1950s and early 1960s would soon unravel as the promises of postcolonial development, justice, and prosperity receded, giving rise to civil unrest and political violence. Rather than promoting a progressive view of history, the three leading Indian filmmakers of the period - Mrinal Sen, Ritwik Ghatak, and Satyajit Ray -- communicated a sense of a postcolonial present characterized by multiple contradictory possibilities. Ray, Sen, and Ghatak's disillusionment from their prior commitment to filmmaking as integral to the development of India anticipated a new way of conceiving ideas of postcolonial history and time that anticipated later works by historians and theorists. Ultimately, these three filmmakers stand out for acknowledging that the postcolonial consensus was in disarray, and with it art cinema's previous certainty about its pedagogic, political, and historic purpose"--